Comparative Analysis of Monolithic and Serverless Microservice Architectures Using Reliability Metrics - Yevhen Mykhailenko (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2026)
This study investigates whether decomposing a Java-based monolithic application into an event-driven serverless design improves resilience. Evaluating reliability metrics like recovery time objective (RTO), recovery point objective (RPO), MTTR, and MTBF against predefined service-level objectives reveals that the serverless variant maintains stable latency under load. It also recovers from injected failures twice as fast as the monolithic baseline. Furthermore, strict serverless execution limits necessitated decomposing long-running tasks into smaller stages, effectively confining failures and maintaining error rates within planned budgets. These findings offer practical guidance for designing highly reliable serverless systems evaluated against explicit service-level objectives.